IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY BERBASIS KEBUTUHAN MASYARAKAT - Sukaris Sukaris (Jurnal Manajerial, 2019)
Although corporate social responsibility has been declared in realizing the three main pillars of development, namely reducing the number of unemployed (pro-job), reducing the number of poor people (pro-poor) and increasing economic growth (pro-growth), however serious efforts need to be made in realizing it, so that community empowerment is based on community needs. The purpose of this study is to determine and analyze the implementation of CSR programs based on community needs. The results of the study show that social responsibility emphasizes the dimensions of developing potential for empowerment and human resource development, institutional cooperation, and sustainable development. The characteristics of the targets of the empowerment program must pay attention to the communities surrounding the company, local potential for growth, capacity building (education and training), the program is sustainable and minimizes charity, provides added value, both economically and socially and to support and synergy with government programs. Identification of the type and level of need empowerment programs that increase independence based on the potential in the community, programs or more specific needs that can be done in a certain period in accordance with the strategic planning and work plan of the company while still based on the performance to be achieved by the company